A Research-Innovation Model to Foster University-Industry Links: An Empirical Typology - Zaibet, Lokman; Gibreel, Tarig; Akhzami, Sheikha; Hedjam, Rachid; Boughanmi, Houcine (Asian Journal of Empirical Research, 2019)
This paper uses a sample of selected research projects in agriculture and food sciences to understand the current research-innovation process and make a first-hand assessment of its impacts or potential output influences. The paper uses cluster analysis to construct a model of research innovation applicable to the fields of agriculture and food and builds the missing links between science and industry. Results demonstrate that most research grants are from the public sector, yet the least targeted are farmers and public institutions. The first targets of research outputs are students and the scientific community. The constructed research-innovation model aims to foster university-industry links; the model displays different stages of research-innovation, where engagement, advocacy, and achievement are compatible with the different dimensions of innovation; in particular the technical, policy, and social dimensions.